(untitled) - Postel, Sandra (Washington, D.C., 2005)
Rivers, lakes, wetlands, and other freshwater ecosystems provide a host of benefits to society. In addition to supplying water and fish, they store seasonal floodwaters, helping to lessen flood damages.
Keywords: Freshwater ecology,Watershed management,Ecosystem management,Water-supply